Surveyed Factors Affecting Lake Tourism Of The Development In Iran (Case Study: Lakes Fars province) - ALiakbar Anabestani; Mahdi Masoumi (تحقیقات کاربردی علوم جغرافیایی)
In the last decade, the lake tourism as one of the newest branches of natural tourism has been under attention of scientific societies. So that this type of tourism has grown significantly and many economic benefits for host communities has brought. The aim of this study is evaluating the factors affecting lake tourism development in Iran. In this regard, a wide variety of indicators in the dimensions of attractions, infrastructure, cultural acceptance, economic, social and environmental In the form of a questionnaire tourism experts and field studies were examined. For binary comparison and a final weight criteria and options, of AHP fuzzy, ANP and GRA techniques in the form of questionnaires and 20 teachers and experts from organizations linked to tourism have been used. The results confirms that: Based on the results of the paired comparison of factors affecting lake tourism of the development using multiple fuzzy AHP and ANP in terms of tourism experts, Criteria attractions by weight of 0.247 in fuzzy AHP and 0.246  in the ANP model and The criteria infrastructural factors weighing 0.229 in fuzzy AHP and 0.234 in the ANP model Has the greatest impact on the lake tourism of development. Finally, with the objective of ranking factors affecting the lake tourism of development in the villages surrounding the lake, using techniques GRA, found that conditions Dowbaneh and dasht Arjan villages are better than other villages and Qashm qavi and Arab Famour villages at the lowest level of lake tourism of  the development have been.